PERLINDUNGAN HUKUM PENGGUNA MARKETPLACE DALAM UPAYA MENGHINDARI RISIKO PENCURIAN DATA PRIBADI - Pratiwi, Ningrum Sekartanjung; Nugraheni, Anjar Sri Ciptorukmi (Jurnal Privat Law, 2025)
AbstractThis article aims to analyze the legal construction of protecting personal data of marketplace users in Indonesia also to analyze the mechanism of protecting personal data of marketplace users based on laws and regulations regarding the implications of the theft of customer data. The article was a normative legal or doctrinal approach to the laws and regulations. The data used secondary data with primary and secondary legal materials. The techniques in the gathering of legal materials were literature study which uses qualitative analysis methods of analysis techniques. Based on the results of the discussion, it can be seen that the legal construction of protecting personal data of marketplace users are regulated in several forms of legislations, namely, the use of personal data must be carried out with the consent of the person concerned, and the protection of personal data is carried out in the process of obtaining, storing, processing, analyzing, displaying, and destroying personal data, and the mechanism used by the government and the organizers (marketplace) to protect the personal data of marketplace users is to have internal rules regarding the protection of user data as a form of prevention to avoid misuse of personal data.AbstrakPenelitian ini bertujuan menganalisis konstruksi hukum perlindungan data pribadi pengguna marketplace di Indonesia dan menganalisis mekanisme perlindungan data pribadi pengguna marketplace berdasarkan peraturan perundang-undangan terkait adanya implikasi dari pencurian data pelanggan. Jenis penelitian ini adalah penelitian hukum normatif atau doktrinal dengan pendekatan perundang-undangan. Penelitian ini menggunakan jenis data sekunder yang bersumber dari bahan hukum primer dan bahan hukum sekunder. Teknik pengumpulan data berupa studi kepustakaan dengan teknik analisis bahan hukum berupa metode analisis kualitatif. Berdasarkan hasil pembahasan dapat diketahui bahwa konstruksi hukum perlindungan data pribadi pengguna marketplace terdapat dalam beberapa peraturan perundang-undangan, yaitu pemanfaatan data pribadi harus dilakukan atas persetujuan orang yang bersangkutan, dan perlindungan data pribadi dilakukan pada proses perolehan, penyimpanan, pengolahan, penganalisisan, penampilan, dan pemusnahan data pribadi, serta mekanisme yang dilakukan oleh pemerintah dan penyelenggara (marketplace) dalam upaya melindungi data pribadi pengguna marketplace adalah dengan memiliki aturan internal mengenai perlindungan data pengguna sebagai bentuk pencegahan untuk menghindari terjadinya penyalahgunaan data pribadi.